Crow, Karim Douglas. “Ta’ṣīl (Foundations) of Peace in the Islamic Discourse,” Translated by Mazen Al-Najjar. Year 7, Issue 25 (Sumer 1422 AH/ 2001 CE), Pp. 79-98. - كرو, كريم دوغلاس; النجار, مازن (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2001)
The rise of Islamic movements in various parts of the Muslim world led to the need for a new discourse that addresses the void between religious tradition and modernity. Unless Muslims are aware of the conditions of modernity and its challenges and historical and contemporary projections, they cannot break free from their oppressors. In their quest for justice, it is imperative for Muslims who critique their own conditions to have a new intellectual discourse that produces a new epistemological foundation for Muslim society. Karim Douglas Crow’s article discusses the thought of the two thinkers Jawdat Saeed and Khalis Chalabi, addressing their work as examples of Islamic discourse on the subject of peace.